Autophagy in the Vertebrate Inner Ear - Magariños, Marta; Pulido, Sara; Aburto, María R.; de Iriarte Rodríguez, Rocío; Varela-Nieto, Isabel (Frontiers in Cell and Developmental Biology, 2017)
Autophagy is a conserved catabolic process that results in the lysosomal degradation of cell components. During development, autophagy is associated with tissue and organ remodeling, and under physiological conditions it is tightly regulated as it plays a housekeeping role in removing misfolded proteins and damaged organelles. The vertebrate inner ear is a complex sensory organ responsible for the perception of sound and for balance. Cell survival, death and proliferation, as well as cell fate specification and differentiation, are processes that are strictly coordinated during the development of the inner ear in order to generate the more than a dozen specialized cell types that constitute this structure. Here, we review the existing evidence that implicates autophagy in the generation of the vertebrate inner ear. At early stages of chicken otic development, inhibiting autophagy impairs neurogenesis and causes aberrant otocyst morphogenesis. Autophagy provides energy for the clearing of dying cells and it favors neuronal differentiation. Moreover, autophagy is required for proper vestibular development in the mouse inner ear. The autophagy-related genes Becn1, Atg4g, Atg5, and Atg9, are expressed in the inner ear from late developmental stages to adulthood, and Atg4b mutants show impaired vestibular behavior associated to defects in otoconial biogenesis that are also common to Atg5 mutants. Autophagic flux appears to be age-regulated, augmenting from perinatal stages to young adulthood in mice. This up-regulation is concomitant with the functional maturation of the hearing receptor. Hence, autophagy can be considered an intracellular pathway fundamental for in vertebrate inner ear development and maturation.